TANGGUNG JAWAB DINAS LINGKUNGAN HIDUP KABUPATEN BATUBARA TERHADAP PENGAWASAN LIMBAH INDUSTRI - Erwin Syahputra; Dwi Armadani; Mazhar Fezliani; Darwin Darwin; Sumardi Nasution; Sabar Rotuah Sitorus (Nusantara Hasana Journal, 2022)
Responsibilities of the Coal Regency Environmental Service for Industrial Waste Supervision. This study examines the content of the Local Government Responsibilities of the Batubara Regency for the supervision of industrial waste. In this legal research, using empirical legal research methods and conducting a study at the Environmental Service Office of Batubara Regency. In this legal research, primary legal materials are used, namely: Legislation. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books. In this study, that the role of the Batubara Regency government does not answer the problems faced by the community, the next Government effort is to provide law enforcement against industries that do not heed the appeals of the Government. In law enforcement which in the perspective of environmental law is expected to be one of the instruments, namely administrative, civil or criminal law instruments, it can even be enforced with all three instruments at once.